EXISTENCE IN THE WORKING ACTIVITY OF MACHINES AND MECHANISMS CAUSES OF UPCOMING SHAKES - Masodiqov, J.X; Sobirov , X.F.; Murtazayev, N.L (Educational Research in Universal Sciences, 2023)
In this article, machines and mechanisms are created in the process of operation the causes of vibration and damping devices were theoretically analyzed.